Identification and Characterization of Novel Perivascular Adventitial Cells in the Whole Mount Mesenteric Branch Artery Using Immunofluorescent Staining and Scanning Confocal Microscopy Imaging - Chandra Somasundaram; Rahul K. Nath; Richard D. Bukoski; Debra I. Diz (International Journal of Cell Biology)
A novel perivascular adventitial cell termed, adventitial neuronal somata (ANNIES) expressing the neural cell adhesion molecule (NCAM) and the vasodilator neuropeptide, calcitonin gene-related peptide (CGRP), exists in the adult rat mesenteric branch artery (MBA) in situ. In addition, we have previously shown that ANNIES coexpress CGRP and NCAM. We now show that ANNIES express the neurite growth marker, growth associated protein-43(Gap-43), palladin, and the calcium sensing receptor (CaSR), that senses changes in extracellular Ca(2+) and participates in vasodilator mechanisms. Thus, a previously characterized vasodilator, calcium sensing autocrine/paracrine system, exists in the perivascular adventitia associated with neural-vascular interface. Images of the whole mount MBA segments were analyzed under scanning confocal microscopy. Confocal analysis showed that the Gap-43, CaSR, and palladin were present in ANNIES about 37 ± 4%, 94 ± 6%, and 80 ± 10% respectively, comparable to CGRP (100%). Immunoblots from MBA confirmed the presence of Gap-43 (48 kD), NCAM (120 and 140 kD), and palladin (90–92 and 140 kD). In summary, CGRP, and NCAM-containing neural cells in the perivascular adventitia also express palladin and CaSR, and coexpress Gap-43 which may participate in response to stress/injury and vasodilator mechanisms as part of a perivascular sensory neural network.